1997
DOI: 10.1007/s002800050737
|View full text |Cite
|
Sign up to set email alerts
|

Piperazine derivatives of butyric acid as differentiating agents in human leukemic cells

Abstract: Butyric acid is a potent antineoplastic agent with a well-documented differentiation activity on a wide variety of tumor cells. However, its clinical development is strongly limited by its very short metabolic half-life. In this study we report on the in vitro effects of new original piperazine derivatives of butyric acid on the induction of differentiation and the growth inhibition of human erythroleukemia K562 cells and myeloid leukemia HL60 cells. 1-(2-hydroxyethyl) 4-(1-oxobutyl)-piperazine (HEPB) and [1-(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…Acetate can reduce the concentration of serum fatty acids, which is an important factor in lowering glucose utilization by tissues and inducing insulin resistance. Long‐term dietary supplementation with propionate was shown to decrease blood glucose in rats and humans, while butyrate possessed antineoplastic properties and is mostly used by colonocytes as an energy source (Gillet et al. 1998; Rizkalla et al.…”
Section: Introductionmentioning
confidence: 99%
“…Acetate can reduce the concentration of serum fatty acids, which is an important factor in lowering glucose utilization by tissues and inducing insulin resistance. Long‐term dietary supplementation with propionate was shown to decrease blood glucose in rats and humans, while butyrate possessed antineoplastic properties and is mostly used by colonocytes as an energy source (Gillet et al. 1998; Rizkalla et al.…”
Section: Introductionmentioning
confidence: 99%
“…Piperizine derivatives were shown to inhibit growth inhibition of human erythroleukemia K5-62 cells and myeloid leukemia HL-60 cells [26] and also shown to inhibit topoisomarase II activity [27]. Wilson et al reported the interaction of DNA with unfused aromatic system containing terminal piperazino substituents [9].…”
Section: Resultsmentioning
confidence: 99%
“…Whilst chemotherapeutic drugs are known to induce autophagy, cell cycle arrest and cell senescence [4,5], it is imperative that there is induction of apoptosis and permanent removal of neoplastic cells for effective cancer chemotherapy. Recently, benzoisothiazole, Isoxazole and piperazine rings have been shown to exhibit varied biological activities including anticancer properties [6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%